Voltage‐sensitive conductances increase the sensitivity of rod photoresponses following pigment bleaching - Pahlberg, Johan; Frederiksen, Rikard; Pollock, Gabriel E.; Miyagishima, Kiyoharu J.; Sampath, Alapakkam P.; Cornwall, M. Carter (The Journal of physiology, 2017)
Key points Following substantial bleaching of the visual pigment, the desensitization of the rod photovoltage is not as substantial as the desensitization of the rod outer segment photocurrent. The block of cation conductances during the internal dialysis of Cs+ further desensitizes the photovoltage thereby eliminating its difference in desensitization with the rod outer segment photocurrent. Bleached visual pigment produced an acceleration of the rod photovoltage with respect to the outer segment photocurrent, which is eliminated upon internal dialysis of Cs+. A majority of our visual experience occurs during the day when a substantial fraction of the visual pigment in our photoreceptor cells is bleached. Under these conditions it is widely believed that rods are saturated and do not contribute substantially to downstream signalling. However, behavioural experiments on subjects with only rod function reveals that these individuals unexpectedly retain substantial vision in daylight. We sought to understand this discrepancy by characterizing the sensitivity of rod photoresponses following exposure to bright bleaching light. Measurements of the rod outer segment photocurrent in transgenic mice, which have only rod function, revealed the well‐studied reduction in the sensitivity of rod photoresponses following pigment bleaching. However, membrane voltage measurements showed that the desensitization of the photovoltage was considerably less than that of the outer segment photocurrent following equivalent pigment bleaching. This discrepancy was largely eliminated during the blockade of cation channels due to the internal dialysis of Cs+, which increased the bleach‐induced desensitization of the photovoltage and slowed its temporal characteristics. Thus, sensitization of the photovoltage by rod inner segment conductances appears to extend the operating range of rod phototransduction following pigment bleaching. Key points Following substantial bleaching of the visual pigment, the desensitization of the rod photovoltage is not as substantial as the desensitization of the rod outer segment photocurrent. The block of cation conductances during the internal dialysis of Cs+ further desensitizes the photovoltage thereby eliminating its difference in desensitization with the rod outer segment photocurrent. Bleached visual pigment produced an acceleration of the rod photovoltage with respect to the outer segment photocurrent, which is eliminated upon internal dialysis of Cs+.